ChemInform Abstract: Preparation of Azidoaryl‐ and Azidoalkyloxazoles for Click Chemistry. Issue 2 (9th January 2013) - Loner, Catherine M.; Luzzio, Frederick A.; Demuth, Donald R.
Abstract Aminative heterocyclization of azido‐substituted esters with ammonium acetate in acetic acid gives the title compounds (II), required for biological evaluation in biofilm inhibition.